Three-dimensional anthropometric study of the facial morphology of black African Senegalese: 3D photogrammetric approach - Sankoung Soumboundou; Mamadou Lamine Ndiaye; N'zebo Marcellin Nouaman; Ons Farhat; Papa Abdou Lecor (Elsevier, 2023)
Introduction: Anthropometric features are important in determining gender and ethnic groups. The aim of this 3D photogrammetric study was to assess the face of Senegalese subjects. Material and methods: A total of 104 3D facial photographs taken with the Bellus 3D application were studied. Measurements were taken at various anthropometric points using Meshlab software. The acquired data were recorded and processed using Jamovi software version 1.8.4.0. Correlations between the quantitative variables were tested and only one with a significance of p 0.05 was retained. Results: Overall, measured distances were higher in men. A statistically significant difference between men and women was found for nose width (p0. 001), face width (p < 0.005) and face height (p0. 0002). Conclusion: 3D anthropometric analysis shows a fairly significant sexual dimorphism, with males having greater facial and nasal proportions. A leptoprosopic (long) facial shape and a mesorrhine nose were maintained.